Integrating literature into the teaching material in the Headway series - Puskás Tekla; Orosz Andrea (2000)
In this thesis I am writing about the connection between language teaching and integrating literature into the teaching material. The most important advantages of teaching literature is that it provides students with enjoyment and genuine samples. Lots of cultural information can be deduced from the works. Alongside with the students' vocabulary enrichment, their reading abilities can be developed and improved. Of course there are disadvantages as well, from which the greatest is that dealing with literary works is very time consuming. If the works covered in class are carefully selected, which involves that the age factor is taken into consideration, the disadvantages can be compensated, or at least it can be achieved that there are more boons than loss. In the third chapter, I am analysing the literary works found in the Headway series, except from the Headway Advanced, as it is not frequently taught in secondary schools. When examining those passages, I am also giving alternatives, solutions to those activities, covering methods that I disliked.
Keywords: Pedagógusképzés